Five Nights at Freddy's : Fazbear Frights - Vol 1 Vol. 1 - Cawthon, Scott, 1971-; Cooper, Elley; West, Carley Anne; Hastings, Chris, 1983- (New York, New York : Graphix, an imprint of Scholastic, 2022)
What do you wish for most? Its a question that Oswald, Sarah, and Oscar think they know the answer to. Oswald wishes his summer wasnt so boring, Sarah wishes to be beautiful, and Oscar wishes to get his hands on the mechanical toy thats out of stock all over town. But in the twisted world of Five Nights at Freddys, their hearts deepest desires have an unexpected cost.
"Teen, ages 12 and up"--Back cover.
Keywords: Robotics -- Comic books, strips, etc; Juvenile fiction; Survival -- Comic books, strips, etc; Juvenile fiction; Murder -- Comic books, strips, etc; Juvenile fiction; Horror comic books, strips, etc. -- Juvenile fiction; Robotics -- Fiction; Survival -- Fiction; Murder -- Fiction; Horror comic books, strips, etc. -- Fiction; Horror comics; Comics adaptations; Graphic novels; Comics (Graphic works)